Clinical Results of Conservative Treatment of Severe Proximal Humerus Fractures Requiring Surgical Treatment in Old Patients. Issue 3 (September 2019) - Pace, Gregory; Zale, Connor; Chan, John; Armstrong, April D.; Boateng, Henry A.; Kim, Hyun-Min
Abstract : The purpose of this study was to investigate the clinical outcomes of nonsurgically treated proximal humerus fractures that would have been otherwise treated surgically had it not been for reasons precluding surgical treatment. A retrospective search for patients treated nonsurgically for a proximal humerus fracture was performed. Injury x-rays of all patients were reviewed independently by 3 orthopedic surgeons. Patients for whom at least 2 surgeons recommended surgical treatment were included. Of 96 eligible patients, 22 patients completed the data collection. There were six 2-part, seven 3-part, five 4-part fractures, and 4 head-split fractures. The mean ASES and QuickDASH scores were 82.7 and 21.9, respectively. The mean VAS pain score was 1.1. No significant effects of head-shaft angles or the presence of a head-split fracture were found. Ultimately, patients with a proximal humerus fracture that would have normally necessitated surgical treatment showed favorable outcomes following nonsurgical treatment. Fracture pattern or articular involvement had no significant effect on the outcomes. This finding suggests that nonsurgical management of proximal humerus fractures that would traditionally necessitate surgical treatment can be a viable option in certain patients whose circumstances preclude surgical treatment.